Strategi dan Model Pemberdayaan Masyarakat Miskin di Sumatera Utara - Yanhar Jamaluddin; Fitriani Fitriani; Safrida Safrida; Warjio Warjio (Universitas Medan Area, 2019)
This article was prepared on the background where the poor in North Sumatera are powerless and have no ability to place their position and role in government and development, whileefforts to empower the poor have not been optimally carried out by the North Sumatera Provincial government. This article was prepared to discuss ways to make the poor in North Sumatera powerless, and outline strategies and models to empower the poor in North Sumatera. The poor are powerless and the risk poses a factor of poverty, physical weakness, isolation, improvement, and powerlessness, the poor are not managed and tend to be left by the government, and are not liked by the community. The strategy for empowering the poor in North Sumatera can be carried out through the Need for Strengthening program, Strengthening Human Resources, Strengthening Institutions, Strengthening Access to Communication and Information, Strengthening Networks - Partnerships, and Strengthening Participation. While the effective model of Poor Community Empowerment in North Sumatera is an Advantage and Change Model (ACM)